MoTe2 Lateral Homojunction Field-Effect Transistors Fabricated using Flux-Controlled Phase Engineering - Ma, Rui; Zhang, Huairuo; Yoo, Youngdong; Degregorio, Zachary Patrick; Jin, Lun; Golani, Prafful; Ghasemi Azadani, Javad; Low, Tony; Johns, James E.; Bendersky, Leonid A.; Davydov, Albert V.; Koester, Steven J. (ACS Nano, 2019)
The coexistence of metallic and semiconducting polymorphs in transition-metal dichalcogenides (TMDCs) can be utilized to solve the large contact resistance issue in TMDC-based field effect transistors (FETs). A semiconducting hexagonal (2H) molybdenum ditelluride (MoTe2) phase, metallic monoclinic (1T′) MoTe2 phase, and their lateral homojunctions can be selectively synthesized in situ by chemical vapor deposition due to the small free energy difference between the two phases. Here, we have investigated, in detail, the structural and electrical properties of in situ-grown lateral 2H/1T′ MoTe2 homojunctions grown using flux-controlled phase engineering. Using atomic-resolution plan-view and cross-sectional transmission electron microscopy analyses, we show that the round regions of near-single-crystalline 2H-MoTe2 grow out of a polycrystalline 1T′-MoTe2 matrix. We further demonstrate the operation of MoTe2 FETs made on these in situ-grown lateral homojunctions with 1T′ contacts. The use of a 1T′ phase as electrodes in MoTe2 FETs effectively improves the device performance by substantially decreasing the contact resistance. The contact resistance of 1T′ electrodes extracted from transfer length method measurements is 470 ± 30 ω·μm. Temperature- and gate-voltage-dependent transport characteristics reveal a flat-band barrier height of 30 ± 10 meV at the lateral 2H/1T′ interface that is several times smaller and shows a stronger gate modulation, compared to the metal/2H Schottky barrier height. The information learned from this analysis will be critical to understanding the properties of MoTe2 homojunction FETs for use in memory and logic circuity applications.
Keywords: Cross sectional transmission electron microscopy; Field effect transistor (FETs); Flat band barrier heights; Homojunction; MoTe2; Schottky barrier heights; Structural and electrical properties; Transition metal dichalcogenides; Chemical vapor deposition; Lateral homojunction; MoTe2; Phase engineering; Schottky barrier height; Transition-metal dichalcogenide